Effects of infertility treatment on anxiety and depression levels - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2019)
Purpose: In this study we aimed to show the most related factors with women's anxiety and depression levels as well find out the differences between primary and secondary infertile women with unexplained reason. Materials and Methods: This was a prospective controlled study of 166 primary and 60 secondary infertile women. They had unexplained infertility and had not any hormonal or uterine pathology. Beck Depression Inventory and Hamilton Anxiety Rating Scale were used for questionnaire. Results: While there were not any differences between two groups for anxiety and depression scores as well for subgroups, secondary infertile women showed a higher rate of severe depression than primary infertile women (11/60 vs. 10/166). While patients' age was correlated with anxiety score, number of treatment attempts was correlated with depression score. Conclusion: Infertility treatment does not have only physical side effects but it has also psychological burden for women. While having a child is very important for some cultures it may not decrease the stress of women whom started infertility treatment and wanted to have more. It is important to support the women whom undergo infertility treatment whether is primary or secondary infertile, while this affect the patient's mood positively as well may increase the success of treatment.
Keywords: Unexplained infertility; woman; depression; anxiety; PSYCHOLOGICAL IMPACT; WOMEN; COUPLES